PEMUNGUTAN PENERIMAAN NEGARA BUKAN PAJAK DALAM KEPUTUSAN MENTERI HUKUM DAN HAK ASASI MANUSIA REPUBLIK INDONESIA UNTUK BADAN HUKUM PERSEROAN TERBATAS MELALUI MEDIA ELEKTRONIK - Detty Fybe Rotty (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2015)
Abstract Withholding tax state revenue is an obligation that must be paid in granting Copies of Ministerial Decree Regarding Approval of the Company Law Board Lost or Damaged and administration Copies Ministerial Decree Concerning the Approval of Amendment to the Articles of Association of the Lost or Damaged, through electronic media Legal Entity Administration System, but in the granting of Ministerial Decree Copies can be printed without any orders to pay for the collection, the regulation does not set the method of payment, so there is a legal vacuum. This journal aims to analyze the legal certainty in the way of non-tax state revenue payments for granting Copies Ministerial Decree Regarding Approval of the Company Law Board Lost or Damaged and administration Copies Ministerial Decree Concerning the Approval of Amendment to the Articles of Association of the Lost or Damaged, through Entity Administration System legal and responsible for the collection of non-tax state revenue not collected in the provision of the copy of the Decree of the Minister ditelah printed. The journal is compiled with normative juridical research method, with the approach of legislation and case approach. Based on the survey results revealed that the legal void makes the legal uncertainty in the manner Revenue collection of non-tax payments for the provision of the copy of the Decree of the Minister of the Missing or Damaged, through the Legal Entity Administration System, so the government should make regulations regarding the manner of payment of non-tax state revenue collection for granting a copy of the Decree of the Minister, and the government in this case the Ministry of Justice and Human Rights fully responsible for the collection of non-tax state revenues not collected. Key words: non-tax revenues, copy the decree of the minister, legal entity administration systemAbstrak Pemungutan Penerimaan Negara Bukan Pajak merupakan kewajiban yang harus dibayar dalam pemberian Salinan Surat Keputusan  Menteri Mengenai Pengesahan Badan Hukum Perseroan yang Hilang atau Rusak dan pemberian Salinan Surat Keputusan Menteri Mengenai Persetujuan Perubahan Anggaran Dasar Perseroan yang Hilang atau Rusak, melalui media elektronik Sistem Administrasi Badan Hukum, namun  dalam pemberian Salinan Surat Keputusan Menteri dapat dicetak tanpa ada perintah untuk membayar pemungutan tersebut, dalam peraturan tidak diatur cara pembayarannya, sehingga ada kekosongan hukum. Jurnal ini bertujuan untuk menganalisis kepastian hukum dalam cara pembayaran Penerimaan Negara Bukan Pajak  untuk pemberian Salinan Surat Keputusan Menteri Mengenai Pengesahan Badan Hukum Perseroan yang Hilang atau Rusak dan pemberian Salinan Surat Keputusan Menteri Mengenai Persetujuan Perubahan Anggaran Dasar Perseroan yang Hilang atau Rusak, melalui Sistem Administrasi Badan Hukum serta yang  bertanggungjawab terhadap pemungutan Penerimaan Negara Bukan Pajak yang tidak dipungut dalam pemberian Salinan Surat Keputusan Menteri yang ditelah dicetak. Jurnal ini disusun dengan metode penelitian yuridis normatif, dengan pendekatan perundang-undangan dan pendekatan kasus. Berdasarkan hasil penelitian diketahui bahwa kekosongan hukum menjadikan ketidakpastian hukum dalam cara pembayaran pemungutan Penerimaan Bukan Pajak untuk pemberian Salinan Surat Keputusan Menteri yang Hilang atau Rusak tersebut, melalui Sistem Administrasi Badan Hukum, sehingga pemerintah harus membuat peraturan mengenai cara pembayaran pemungutan Penerimaan Negara Bukan Pajak untuk pemberian Salinan Surat Keputusan Menteri tersebut, serta  pemerintah dalam hal ini Kementerian Hukum Dan Hak Asasi Manusia bertanggungjawab sepenuhnya terhadap pemungutan Penerimaan Negara Bukan Pajak  yang tidak dipungut.   Kata kunci: penerimaan negara bukan pajak, salinan surat keputusan menteri, sistem administrasi badan hukum